PENGARUH MOTIVASI, PERSEPSI KUALITAS PRODUK, DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA VARIO DI CV. CENDANA WANGI BATANG - Dimas Ilham Ananko, 13.05.51.0122 (Students Journal of Economic and Management, 2017)
CV. Cendana Wangi Batang is a Honda sales dealer in Batang city, Honda Vario sales in CV. Cendana Wangi Batang from January to December fluctuated in 2016, an increase in May, June, July, November and December. The decrease occurred in February, March, August, and October, in terms of purchasing decisions made by consumers of course they are influenced by various variables. There are several variables that influence purchasing decisions from previous research such as motivation, product quality perceptions, reference groups, brand personality, promotions, prices, and consumer attitudes. However, in this study only limited the variables of motivation, perception of product quality, and consumer attitudes. This purpose of this study was to analysis the effect of motivation, perception of quality, and attitudes of consumers to purchase decisions on the CV. Cendana Wangi Batang. Population in this research is owner and buyer of Honda Vario motorcycle in CV. Cendana Wangi Batang with the criteria of owner and buyer of Honda Vario motorcycle with minimum age of 21 years. The number of samples studied is as many as 100 people selected as respondents by using purposive sampling technique. Data collection methods used in this study is a questionnaire filled by respondents. Analysis technique used in this research is validity test, reliability test, classical assumption test, multiple linear regression test, model feasibility test, hypothesis significance test. Data processing using SPSS Version 22. The results of this study showed that the motivation, perception of quality, and attitudes of consumers have a positive and significant influence on purchasing decisions Keywords : Motivation, Quality Perception product,Consumer Attitudes, and Purchasing Decision.